2018
DOI: 10.1016/j.combustflame.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen shift isomerizations in the kinetics of the second oxidation mechanism of alkane combustion. Reactions of the hydroperoxypentylperoxy OOQOOH radical

Abstract: Hydroperoxyalkylperoxy species are important intermediates that are generated during the autoignition of transport fuels. In combustion, the fate of hydroperoxyalkylperoxy is important for the performance of advanced combustion engines, especially for autoignition. A key fate of the hydroperoxyalkylperoxy is a 1,5 H-shift, for which kinetics data are experimentally unavailable. In the present work, we study 1hydroperoxypentan-3-yl)dioxidanyl (CH3CH2CH(OO)CH2CH2OOH) as a model compound to clarify the kinetics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 82 publications
2
35
0
Order By: Relevance
“…In our work on other reactive systems, we observed that this maximum arises at lower temperatures as the number of atoms in the involved molecules increases and is not particular of the system under investigation: it has been also described by other authors in the study of the hydrogen shift isomerization of oxygenated C 5 hydrocarbons. 37 …”
Section: Resultsmentioning
confidence: 99%
“…In our work on other reactive systems, we observed that this maximum arises at lower temperatures as the number of atoms in the involved molecules increases and is not particular of the system under investigation: it has been also described by other authors in the study of the hydrogen shift isomerization of oxygenated C 5 hydrocarbons. 37 …”
Section: Resultsmentioning
confidence: 99%
“…The reactants, transition states, and products in the studied mechanistic branches of the isoprene chemistry were characterized at the M06-2X and CCSD(T) levels of theory. The conformer space for each of these structures was characterized at the M06-2X/cc-pVDZ level of theory (Dunning, 1989;Zhao and Truhlar, 2008;Alecu et al, 2010;Bao et al, 2017), locating ∼ 24 000 distinguishable structures from ∼ 60 000 systematically generated starting geometries. The most relevant conformers (∼ 850 structures across all reactions examined) were then fully re-optimized at the M06-2X/aug-cc-pVTZ level of theory (Dunning, 1989).…”
Section: Quantum Chemical and Theoretical Kinetic Calculationsmentioning
confidence: 99%
“…The lower energy barriers of the effective aldehyde-Hmigration processes imply that the acyl radical tri-HPACYL is formed with a significantly lower energy content, 17-19 kcal mol −1 , than estimated by Peeters et al (2014), reducing the likelihood of chemically activated decomposition. Note that the H-migration reactions are typically found to be in the high-pressure limit (Miyoshi, 2012;Peeters et al, 2014;Xing et al, 2018;Møller et al, 2019), and multistep chemical activation does not contribute significantly. Furthermore, we found that the CO elimination barrier in tri-HPACYL-I, ∼ 8 kcal mol −1 (see Table S1), is higher than estimated by Peeters et al (2014) (≤ 7 kcal mol −1 ), further hampering prompt decomposition.…”
Section: Elimination Of Co From Tri-hydroperoxy Acyl Radicalsmentioning
confidence: 99%
“…Full presentations of the pressure-dependent SS-QRRK model for an irreversible unimolecular reaction are given in our previous paper 32 and in a recent review 40 for the case where the mechanism assumed is to be…”
Section: Details: Pressure Dependencementioning
confidence: 99%
“…Three prototypical OOQOOH species and the corresponding reactions of [1,5] H-shift. A and B are studied here and C are studied in the previous article 32 .…”
Section: Introductionmentioning
confidence: 99%